Hypoxia causes transgenerational impairments in reproduction of fish - Simon Yuan Wang (Nature Portfolio, 2016)
Hypoxia has diverse effects on aquatic life. Wang et al.show that reproductive defects resulting from hypoxia are epigenetically heritable in Japanese rice fish, and that this intergenerational inheritance is accompanied by differential methylation and gene expression in sperm.